Microclimate Data Measured at Unmanned Observation Station, the Yukidori Valley, Langhovde, Antarctica in 1988-1989 - OHTANI, Shuji; KANDA, Hiroshi; INO, Yoshio (National Institute of Polar Research, 1991)
P(論文) departmental bulletin paper